Peran Pustakawan Dalam Meningkatkan Layanan Informasi di Perpustakaan FEB Universitas Negeri Padang - Azzahra, Nadia Fatma; Nabila, Jeihan (Universitas Negeri Padang, 2023)
User satisfaction can be achieved if the library provides good quality service. Therefore, libraries must focus on user satisfaction. To be able to find out the services that users want, need and expect, it is necessary to conduct research on users. This is done so that there is no difference in perception regarding what the library provides to users and what users actually want and need. Based on the problems above, the research aims to analyze the quality of services provided by the Padang State University FEB Library using the ServQual method. In the ServQual model, the user's perception of the service received (perceived service) is the result of a series of internal company decisions and activities. The quality of service provided by Padang State University FEB Library still cannot satisfy customers. This can be seen from the negative gap value of the ServQual score. Of the 23 service attributes, there are 13 attributes that have a negative value that cannot be accepted by users and 10 attributes that can still be tolerated by users.